Working-time options over the life course: New challenges to German companies in times of crisis - Philip Wotschack (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2010)
The significance of life-course oriented approaches to working-time organisation is heightened in the current context of demographic change and profound transformations in the system of gainful employment and employment biographies. The aim of these approaches is to create new and better ways for employees to adapt their working time to their changing needs over the life course to have time for providing care and nursing, and for recreation and further education. This paper uses empirical examples of long-term or working-life time accounts to examine whether and under which conditions these approaches are actually implemented in company practice. It also outlines new risks and challenges raised by the recent economic crisis. First, current demands regarding the organisation of working time are outlined and new approaches to life-course oriented working-time policy are presented. The opportunities and restrictions associated with individual options for the organisation of the working lifetime are then discussed on the basis of recent research results on the distribution and utilisation of working-life time accounts. The results indicate that there are significant barriers to and difficulties with the implementation of working-life time accounts. They underline the need for an integrated approach to life-course oriented working-time organisation that links individual workingtime options with working-time reductions and active employment policy at both the company and collective-bargaining and statutory levels (Section 5). – – Vor dem Hintergrund des demografischen Wandels und tiefgreifender Veränderungen im System der Erwerbsarbeit und Erwerbsverläufe erhalten lebenslauforientierte Ansätze der Arbeitszeitgestaltung eine große Bedeutung. Sie sollen für die Beschäftigten neue Möglichkeiten eröffnen, um die Erwerbsarbeitszeit besser an die im Lebenslauf wechselnden Betreuungs-, Pflege-, Erholungs- und Weiterbildungsbedarfe anzupassen. Der Artikel untersucht am empirischen Beispiel von Lebensarbeitszeit- oder Langzeitkonten, ob und unter welchen Voraussetzungen diese Möglichkeit in der betrieblichen Praxis tatsächlich realisiert wird. Dazu werden zunächst aktuelle Anforderungen an die Arbeitszeitgestaltung skizziert und neue Ansätze der lebenslauforientierten Arbeitszeitpolitik vorgestellt. Die Möglichkeiten und Grenzen von individuellen Optionen zur Gestaltung der Lebensarbeitszeit werden anhand aktueller Forschungsergebnisse zur Verbreitung und Nutzung von Langzeitkonten diskutiert. Die Ergebnisse deuten auf erhebliche Barrieren und Schwierigkeiten beim Einsatz von Langzeitkonten hin. Sie unterstreichen die Notwendigkeit eines integrierten Ansatzes der lebenslauforientierten Arbeitszeitgestaltung, der auf betrieblicher und überbetrieblicher Ebene individuelle Arbeitszeitoptionen mit niedrigeren Arbeitszeitstandards und aktiver Beschäftigungspolitik verbindet.
Keywords: 330; Arbeitszeitgestaltung; Lebensverlauf; Familie-Beruf; Wirtschaftskrise; Deutschland